2016
DOI: 10.1002/2015ja022260
|View full text |Cite
|
Sign up to set email alerts
|

Ionosonde tracking of infrasound wavefronts in the thermosphere launched by seismic waves after the 2010 M8.8 Chile earthquake

Abstract: Ionospheric disturbances associated with the M8.8 Chile earthquake (35.91°S, 72.73°W) on 27 February 2010 were observed at Kazan, Russia (55.85°N, 48.81°E). Rapid‐run ionograms at 1 min intervals exhibited multiple‐cusp signatures (MCSs) for more than 30 min, which have been observed several times after large earthquakes. The ionospheric disturbances were caused by infrasound propagating upward in the atmosphere, which modified the electron density distribution through ion‐neutral collisions. The anomaly of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…(Maruyama et al, 2016). The difference between the epicentral distances for Obninsk and Kazan was approximately 773 km.…”
Section: Observationsmentioning
confidence: 99%
“…(Maruyama et al, 2016). The difference between the epicentral distances for Obninsk and Kazan was approximately 773 km.…”
Section: Observationsmentioning
confidence: 99%
“…Rayleigh wave signatures in the ionosphere following earthquakes have been measured by Doppler sounding (e.g., Yuen et al 1969;Tanaka et al 1984;Artru et al 2004;Chum et al 2016) using TEC measurements (e.g., Ducic et al 2003;Astafyeva et al 2009;Rolland et al 2011) and the inspection of ionograms (Maruyama et al 2012(Maruyama et al , 2016a(Maruyama et al , 2016b.…”
Section: Introductionmentioning
confidence: 99%
“…The increased temporal resolution of the ionosonde allows us to consider the background ionosphere at the averaging period to be stationary and to persistently find tracks of 1-15 min ionospheric irregularities on ionograms. Using the proposed method and data from the ISTP SB RAS fast chirp ionosonde, located near Irkutsk [Podlesny, 2017;Naumenko, Podlesny, 2017], we have obtained the statistics of the distribution of irregularities by observed velocities for a given region; we have shown that there is an appreciable number of 1-15 min irregularities moving downward with a characteristic observed vertical velocity of ~160 m/s, which in the first approximation does not depend on season.…”
Section: Introductionmentioning
confidence: 99%
“…These irregularities are sometimes associated with acoustic waves from various powerful sources and can propagate from a source both horizontally [Berngardt et al, 2015a] and vertically [Maruyama et al, 2016a[Maruyama et al, , 2016bBerngardt et al, 2015bBerngardt et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation